Infliximab and etanercept have distinct actions but similar effects on cytokine profiles in rheumatoid arthritis - Takeshita, Masaru; Suzuki, Katsuya; Kikuchi, Jun; Izumi, Keisuke; Kurasawa, Takahiko; Yoshimoto, Keiko; Amano, Koichi; Takeuchi, Tsutomu (Cytokine (Philadelphia, Pa.), 2015)
•We compared serum cytokines in RA patients treated by infliximab and etanercept.•Serum IL-6 is decreased by etanercept and infliximab treatment to the same degree.•Serum IFNγ and TNFβ are increased by infliximab treatment.•IFNγ increase is a distinctive feature of the inefficacy of infliximab treatment. Pro-inflammatory cytokines, especially TNFα, play a central role in the pathogenesis of rheumatoid arthritis (RA). The available TNF inhibitors are only slightly different from one another in terms of clinical efficacy, at least at the group level, but their structures and modes of action are not identical. Infliximab (IFX) and etanercept (ETN) differ in their ability to induce antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity, and in their ability to bind TNFβ. The purpose of our study was to elucidate the different cytokine pathways through which these two drugs enact their clinical efficacy. Serum from 44 RA patients treated with IFX and 24 patients treated with ETN was studied. All patients had been given these biologics at identical dosages and intervals for one year. The concentrations of 11 inflammatory cytokines and their receptors (IL-1β, IL-2, IL-6, IL-6R, IL-8, IL-10, IL-12, TNFα, TNFβ, IFNγ, and GM-CSF) were measured at weeks 0, 22, and 54 using a high-sensitivity electro-chemiluminescence assay. Cytokine profiles were analyzed along with clinical efficacy. IL-6 was significantly decreased in the ETN+MTX and IFX+MTX groups, although not in the ETN-only group; this change was consistent with changes in disease activity. IFNγ was gradually increased only in the non-remission subgroup of the IFX group, and not at all in the ETN group. TNFβ increased after starting IFX regardless of clinical efficacy. IL-6 inhibition is a pathway affected by both IFX and ETN. In addition, IFNγ increase is a distinctive feature of the inefficacy of IFX.